AI-enabled monitoring of compound coastal hazards in Middle Eastern arid mangroves: evidence, readiness and pathways to early warning - Gowhar Meraj; Mohamed Y Abouleish; Shizuka Hashimoto; Rabin Chakrabortty; Tarig Ali (Current Opinion in Environmental Sustainability, 2026)

Veining style and size-scaling behavior throughout the generation and exhumation of subduction mélange: Evidence from Japan and Alaska - J.N. Hooker; S. Luciano; D.M. Fisher; A.J. Smye; Y. Hashimoto; T. Hosokawa; S.J. Elliott (Journal of Structural Geology, 2026)

Mitochondrial orf463 causing male sterility in radish is possessed by cultivars belonging to the ‘Niger’ group - H. Yamagishi; Y. Tanaka; S. Shiiba; A. Hashimoto; A. Fukunaga; T. Terachi (Euphytica, 2019)

Impact of bacterial coinfection on clinical outcomes in pneumococcal pneumonia - S. Kumagai; T. Ishida; H. Tachibana; Y. Ito; A. Ito; T. Hashimoto (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

A large hydrothermal reservoir beneath Taal Volcano (Philippines) revealed by magnetotelluric resistivity survey: 2D resistivity modeling - Y. Yamaya; P. K. B. Alanis; A. Takeuchi; J. M. Cordon; T. Mogi; T. Hashimoto; Y. Sasai; T. Nagao (Bulletin of Volcanology, 2013)

Characteristics and osteogenic differentiation of stem/progenitor cells in the human dental follicle analyzed by gene expression profiling - H. Aonuma; N. Ogura; K. Takahashi; Y. Fujimoto; S. Iwai; H. Hashimoto; K. Ito; Y. Kamino; T. Kondoh (Cell and Tissue Research, 2012)

‘Better off alone than in bad company’: agonistic colour display in mimetic juveniles of two ephippid species - B. Barros; Y. Sakai; H. Hashimoto; K. Gushima; M. Vallinoto (Journal of Fish Biology, 2012)
Comparative field observations of agonistic interactions in juvenile leaf‐mimicking Platax orbicularis and Chaetodipterus faber (Ephippidae) were conducted in coastal waters of the Pacific and Atlantic Oceans. Similar agonistic behaviour was observed in the two species, in which individuals stopped displaying their mimetic colouration during encounters with conspecifics, to display conspicuous colours, such as transverse stripes along the body. These events were observed occasionally, almost invariably in individuals of smaller body size. Larger‐bodied individuals of both species spent less time in agonistic displays. The absolute size of the fish, however, did not appear to affect the outcome of the encounter, suggesting that dominance is a temporary condition, based on the relative size of the opponents during encounters.

Antifouling properties of tough gels against barnacles in a long-term marine environment experiment - T. Murosaki; T. Noguchi; K. Hashimoto; A. Kakugo; T. Kurokawa; J. Saito; Y. M. Chen; H. Furukawa; J. P. Gong (Biofouling, 2009)

Nucleotide sequence analysis of seven Japanese isolates of Plantago asiatica mosaic virus (PlAMV): a unique potexvirus with significantly high genomic and biological variability within the species - K. Komatsu; Y. Yamaji; J. Ozeki; M. Hashimoto; S. Kagiwada; S. Takahashi; S. Namba (Archives of Virology, 2008)

Complete nucleotide sequence of asparagus virus 3 - M. Hashimoto; J. Ozeki; K. Komatsu; H. Senshu; S. Kagiwada; T. Mori; Y. Yamaji; S. Namba (Archives of Virology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genome sequence of a Japanese isolate of Radish mosaic virus: the first complete nucleotide sequence of a crucifer-infecting comovirus - K. Komatsu; M. Hashimoto; K. Maejima; J. Ozeki; S. Kagiwada; S. Takahashi; Y. Yamaji; S. Namba (Archives of Virology, 2007)

Horizontal and Vertical Distribution of Estrogenic Activities in Sediments and Waters from Tokyo Bay, Japan - S. Hashimoto; A. Horiuchi; T. Yoshimoto; M. Nakao; H. Omura; Y. Kato; H. Tanaka; K. Kannan; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 2005)

Current Levels of Dioxins in Surface Soils from Santiago, Chile - Y. Takazawa; R. Verdugo; P. Richter; K. Kitamura; J.-W. Choi; S. Hashimoto; H. Ito; Y. Shibata; M. Morita (Bulletin of Environmental Contamination and Toxicology, 2004)

High frequency Agrobacterium-mediated transformation and plant regeneration via direct shoot formation from leaf explants in Beta vulgaris and Beta maritima - H. Hisano; Y. Kimoto; H. Hayakawa; J. Takeichi; T. Domae; R. Hashimoto; J. Abe; S. Asano; A. Kanazawa; Y. Shimamoto (Plant Cell Reports, 2004)

Phylogenetic relationships of deep-sea mussels of the genus Bathymodiolus (Bivalvia: Mytilidae) - J.-I. Miyazaki; M. Shintaku; A. Kyuno; Y. Fujiwara; J. Hashimoto; H. Iwasaki (Marine Biology, 2004)

In situ pressure–temperature conditions of a tectonic mélange: Constraints from fluid inclusion analysis of syn‐mélange veins - Y. Hashimoto; M. Enjoji; A. Sakaguchi; G. Kimura (Island Arc, 2003)
Pressure and temperature (P–T) conditions of mélange formation are estimated from fluid inclusions within “syn‐mélange” veins developed in the necks of boudins of sandstone blocks in the mélange of the Shimanto accretionary complex, south‐west Japan. The mélange records décollement‐zone processes. P–T conditions are in the range of 81 (+15) to 235 (±18) MPa and 150 (±25) to 220 (±31)°C. Assuming a constant fluid‐pressure to lithostatic‐pressure ratio for each data set, we estimate a P–T gradient of between 10.0°C/km (+0.2/−1.5) (lithostatic pressure) and 4.2°C/km (+0.1/−0.9) (hydrostatic pressure) from these results. The estimated lithostatic P–T gradient is much lower than that calculated from the age of the subducting oceanic plate. The estimated P–T conditions suggest that the mélange was formed within the seismogenic zone (hypothesized from thermal modeling), although the deformation mechanism of mélange (i.e. dominant diffusive mass transfer mainly in shale matrix with minor brittle breakage mainly in sandstone blocks) does not show evidence of seismic deformation. In addition, at the time of syn‐mélange vein formation, a shale matrix of mélange has injected into the vein, which indicates a ductile deformation of shale. A possible explanation for this discrepancy is that the mélange was formed during the interseismic period.

Sleeping mound construction using coral fragments by the rockmover wrasse - S. Takayanagi; Y. Sakai; H. Hashimoto; K. Gushima (Journal of Fish Biology, 2003)
The rockmover wrasse Novaculichthys taeniourus was observed using coral fragments for mound construction on the reefs of Kuchierabu‐jima Island, Japan. The wrasse heaped between four and 71 pieces of coral fragments on each sand mound, and dived into the mound just before sunset. Coral fragments may facilitate the retention of sleeping sites under competition with other sand‐diving wrasses.

Peripheral nerve regeneration through alginate gel: analysis of early outgrowth and late increase in diameter of regenerating axons - T. Hashimoto; Y. Suzuki; M. Kitada; K. Kataoka; S. Wu; K. Suzuki; K. Endo; Y. Nishimura; C. Ide (Experimental Brain Research, 2002)

Molecular taxonomy of vestimentiferans of the western Pacific and their phylogenetic relationship to species of the eastern Pacific - Kojima S.; Ohta S.; Yamamoto T.; Miura T.; Fujiwara Y.; Fujikura K.; Hashimoto J. (Marine Biology, 2002)

3. Histaminergic mechanisms in the brain¶Possible involvement of the chorda tympani nerve in stimulation of the histaminergic system by leptin - T. Morimoto-Ishizuka; Y. Treesukosol; Y. Yamamoto; K. Yamamoto; T. Hashimoto; A. Yamatodani (Inflammation Research, 2002)

Critical involvement of CD40 in protection against herpes simplex virus infection in a murine model of genital herpes - K. Inagaki-Ohara; T. Kawabe; Y. Hasegawa; N. Hashimoto; Y. Nishiyama (Archives of Virology, 2002)

Molecular taxonomy of vestimentiferans of the western Pacific and their phylogenetic relationship to species of the eastern Pacific. I. Family Lamellibrachiidae - Kojima S.; Ohta S.; Yamamoto T.; Miura T.; Fujiwara Y.; Hashimoto J. (Marine Biology, 2001)

Hemagglutinin genotype profiles of canine distemper virus from domestic dogs in Japan - M. Hashimoto; Y. Une; M. Mochizuki (Archives of Virology, 2001)

In vitro characterization of J-113397, a non-peptide nociceptin/orphanin FQ receptor antagonist - R. Bigoni; G. Calo'; A. Rizzi; R. Guerrini; C. De Risi; Y. Hashimoto; E. Hashiba; D.G. Lambert; D. Regoli (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

A major metabolite of aceclofenac, 4′-hydroxy aceclofenac, suppresses the production of interstitial pro-collagenase/proMMP-1 and pro-stromelysin-1/proMMP-3 by human rheumatoid synovial cells - R. Yamazaki; S. Kawai; Y. Mizushima; T. Matsuzaki; S. Hashimoto; T. Yokokura; A. Ito (Inflammation Research, 2000)

Retrolyc1-1, a member of the Tntl retrotransposon super-family in the Lycopersicon peruvianum genome - Ana Paula P. Costa; Katia C. Scortecci; Regina Y. Hashimoto; Paula G. Araujo; Marie-Angele Grandbastien; Marie-Anne Van Sluys (Genetica, 1999)

Genetic contribution of the BAT2 gene microsatellite polymorphism to the age-at-onset of insulin-dependent diabetes mellitus - M. Hashimoto; N. Nakamura; H. Obayashi; F. Kimura; A. Moriwaki; G. Hasegawa; H. Shigeta; Y. Kitagawa; K. Nakano; M. Kondo; M. Ohta; M. Nishimura (Human Genetics, 1999)

Genetic contribution of the BAT2 gene microsatellite polymorphism to the age-at-onset of insulin-dependent diabetes mellitus - M. Hashimoto; N. Nakamura; H. Obayashi; F. Kimura; A. Moriwaki; G. Hasegawa; H. Shigeta; Y. Kitagawa; K. Nakano; M. Kondo; M. Ohta; M. Nishimura (Human Genetics, 1999)

Enhanced human tumor cell transplantability in a new congenic immunodeficient mouse; KSN-BNX - Y. Ishigaki; K. Yasuda; N. Hashimoto; H. Nikaido; O. Nikaido; J. -I. Hayakawa (Folia Microbiologica, 1998)

Molecular systematics of vestimentiferan tubeworms from hydrothermal vents and cold-water seeps - M. B. Black; K. M. Halanych; P. A. Y. Maas; W. R. Hoeh; J. Hashimoto; D. Desbruyères; R. A. Lutz; R. C. Vrijenhoek (Marine Biology, 1997)

Production and recovery of an enzyme fromPseudomonas vesicularis var.povalolyticus PH that degrades polyvinyl alcohol - Y. Kawagoshi; Y. Mitihiro; M. Fujita; S. Hashimoto (World Journal of Microbiology and Biotechnology, 1997)

Effects of carp serum on the growth of goldfish fin cells in early passage - H. Hashimoto; H. Toyohara; Y. Yokoyama; M. Sakaguchi; K. Ozato; Y. Wakamatsu (Journal of Fish Biology, 1997)
The culture medium supplemented with carp serum and fetal bovine serum (FBS) promoted cell growth significantly and induced morphological change of goldfish fin cells in early passage as compared to the medium containing FBS alone. However, these effects were not observed in RBCF‐1, a cell line established from the goldfish fin. The sensitivity of the cells in early passage to carp serum suggests the following possibilities: (1) cells in early passage retain the ability to respond to growth‐promoting factors specifically included in carp serum; and (2) this ability is lost during the process of long‐term culture and/or long‐term culture in FBS eliminates cell groups showing high dependency of cell growth on carp serum.

Lactoferrin-mediated protection of the host from murine cytomegalovirus infection by a T-cell-dependent augmentation of natural killer cell activity - K. Shimizu; H. Matsuzawa; K. Okada; S. Tazume; S. Dosako; Y. Kawasaki; K. Hashimoto; Y. Koga (Archives of Virology, 1996)

Analysis of target organs for the latency of murine cytomegalovirus DNA using specific pathogen free and germfree mice - H. Matsuzawa; K. Shimizu; K. Okada; K. Ando; K. Hashimoto; Y. Koga (Archives of Virology, 1995)

Identification of mutation sites of a temperature-sensitive mutant of HCMV DNA polymerase activity - S. Ihara; M. Takekoshi; N. Mori; S. Sakuma; J. Hashimoto; Y. Watanabe (Archives of Virology, 1994)

Unusual splice sites in the E1A?E1B cotranscripts synthesized in adenovirus type 40-infected A549 cells - S. Ishida; Y. Fujinaga; K. Fujinaga; N. Sakamoto; S. Hashimoto (Archives of Virology, 1994)

Evidence for the presence of a genome-linked protein in infectious flacherie virus - Y. Hashimoto; A. Watanabe; S. Kawase (Archives of Virology, 1986)